Game analyses of futsal and outdoor soccer - A comparison - Althoff, K.; Pisano, K.; Reich, M.; Hennig, E. M. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Futsal is the official indoor soccer game approved by FIFA and it becomes more and more popular all over the world. The specific rules of the game (low bounce ball, no walls, etc.) lead to a different way of playing soccer, compared to other small-sided or outdoor games. The aim of this study was to analyze playing characteristics of the futsal game and compare them to outdoor matches. Methods 10 matches of the official FIFA futsal world championship 2008 in Brazil were analyzed from video recordings of the broadcast stations. Player movements nearby the ball and each action with the ball were characterized and localized on the playing field. In doing this used kicking techniques were recorded. Shots on goal and goalkeeper actions were analyzed separately. These results were compared to data from matches of the men`s soccer world cup games in (Korea, Japan) 2002 1.. Results & Discussion More than twice the number of player actions per minute were found for futsal. In futsal 92% of all actions with ball are passing the ball over a short distance (49%) and controlling the ball (43%). Futsal players use very frequently the inside kick and the sole of the shoe (figure 1). The toepoke is often used for shots on goal in futsal (19%). This technique is used rarely in outdoor soccer. Because of the greater distances in outdoor soccer players shoot much more often with the full instep on the goal (60%) as compared to futsal (21%). Conclusion Compared to outdoor soccer futsal is a highly intensive game with more than twice as much actions with the ball on a small field. To be successful in futsal very different kicking techniques and team strategies are applied. Our data may be helpful in footwear design for futsal players.